ETHORICOXIB IN THE TREATMENT OF RHEUMATIC DISEASES - Yu A Olyunin; Yu A Olyunin (Современная ревматология, 2010)
Ethoricoxib is a new-generation selective COX-2 inhibitor. It has been recently licensed in Russia for the treatment of osteoarthrosis (OA), rheumatoid arthritis (RA), ankylosing spondylitis (AS), and acute gouty arthritis. The drug is supplied as 60-, 90-, and 120-mg tablets. It is given once daily. It is used in a dose of 60 mg/day for long-term therapy for OA, 90 mg/day for RA, and 120 mg/day for the arrest of acute gouty arthritis (for not more than 8 days). The high efficacy and good tolerability of ethoricoxib have been proven by numerous clinical trials and the drug is being extensively used to treat OA, RA, AS, and acute gouty arthritis. It is also successfully used in low back pain and dysmenorrhea. A number of clinical trials have demonstrated that ethoricoxib is well tolerated; it substantially increases quality of life and may be successfully used in the long-term therapy of rheumatic diseases. Moreover, it may cause much fewer adverse gastrointestinal reactions than may nonselective nonsteroidal anti-inflammatory drugs.